1995
DOI: 10.1097/00005373-199501000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Compartment Syndrome

Abstract: Abdominal compartment syndrome is still a controversial entity. We report on a patient who developed the classical hemodynamic, respiratory, and renal changes of abdominal compartment syndrome after surgical intervention for blunt abdominal trauma. A decompressive laparotomy improved the situation dramatically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…Abdominal compartment syndrome became recognized as a cause of significant morbidity and mortality in the late 1980s, particularly in cases of trauma and vascular surgery [11,12]. Small increases in intraabdominal pressure can result in renal and respiratory failure, as well as impaired venous return.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal compartment syndrome became recognized as a cause of significant morbidity and mortality in the late 1980s, particularly in cases of trauma and vascular surgery [11,12]. Small increases in intraabdominal pressure can result in renal and respiratory failure, as well as impaired venous return.…”
Section: Discussionmentioning
confidence: 99%
“…Noradrenaline, endothelin-1, and angiotensin II are all vasoconstrictive agents. We do not know for sure, however, if the renal vasoconstriction that occurs under increased IAP is due to one or more of these hormones, or to other agents.Several studies [1,12,20] have shown that increased IAP results in reduced urinary output or anuria and that this condition can be reversed by abdominal decompression. The diuresis is regulated by several factors, such as renal blood flow, glomerular filtration rate, and reabsorption of sodium and water [11].…”
mentioning
confidence: 99%
“…Several studies [1,12,20] have shown that increased IAP results in reduced urinary output or anuria and that this condition can be reversed by abdominal decompression. The diuresis is regulated by several factors, such as renal blood flow, glomerular filtration rate, and reabsorption of sodium and water [11].…”
mentioning
confidence: 99%
“…[1][2][3] The exact pressure thresholds that signify both intra-abdominal hypertension (IAH) and correlate with ACS are controversial. Its precise incidence in critically ill patients is also unclear, but most likely approximates 1% to 14% depending on the population.…”
Section: Discussionmentioning
confidence: 99%